The philosophy of Vladimir Solovyov as the subject matter of Yuri Govorukha-Otrok’s literary criticism - Zakharova, Elizaveta (Studies in East European thought, 2020)
Vladimir Solovyov’s aesthetic theory has been the subject of much research. However, aesthetic views of the philosopher’s contemporaries are analyzed less frequently. The purpose of this article is to consider the views of Yuri Govorukha-Otrok on the aesthetic ideas of Solovyov in relation to the issues of national identity. Despite the discrepancy in the interpretation of such concepts as “culture,” “national idea,” or “truth” the very fact of the polemics between the philosopher and the literary critic proves the continuity of the religious and the philosophical dimensions of literary criticism. This study analyzes Govorukha-Otrok’s critical papers of Solovyov’s work, allowing for the possibility to compare integral ideological and philosophical systems in order to understand the influence of Govorukha-Otrok’s views on the whole body of Solovyov’s ideas.